2020
DOI: 10.3390/tropicalmed5040167
|View full text |Cite
|
Sign up to set email alerts
|

Quality, Equity and Utility of Observational Studies during 10 Years of Implementing the Structured Operational Research and Training Initiative in 72 Countries

Abstract: Introduction: Observational studies are often inadequately reported, making it difficult to assess their validity and generalizability and judge whether they can be included in systematic reviews. We assessed the publication characteristics and quality of reporting of observational studies generated by the Structured Operational Research and Training Initiative (SORT IT). Methods: A cross-sectional analysis of original publications from SORT IT courses. SORT IT is a global partnership-based initiative aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…The core aspects of the SORT IT training model have been described before [ 14 ]. In brief, front-line health workers and decision makers acquire the theoretical and practical skills for conducting operational research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core aspects of the SORT IT training model have been described before [ 14 ]. In brief, front-line health workers and decision makers acquire the theoretical and practical skills for conducting operational research.…”
Section: Methodsmentioning
confidence: 99%
“…Both STROBE and COREQ guidelines include checklists, which help assess the completeness and quality of reporting into its program. A previous assessment of 392 observational studies from SORT IT projects in 72 countries revealed excellent reporting according to STROBE standards, the average score exceeding 85% [ 14 ]. No such assessment has been performed on mixed methods and qualitative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 12 years, we have used the SORT IT (Structured Operational Research and Training Initiative) model to build capacity in programmatic or public health officers in low- and middle-income countries to undertake and publish operational research using routinely collected data [ 39 ]. This has been remarkably successful, resulting in many high-quality observational studies being undertaken and published in open access journals and adhering to STROBE guidelines [ 40 ].…”
Section: Making Real-time Operational Research Happen and Ensuring It Is Effectivementioning
confidence: 99%
“…However, this type of research can be utilized for many other different diseases. A review of published papers through the SORT IT model between 2009 and 2018 showed that while 45% of operational research projects were on TB, the remainder were on other communicable diseases, non-communicable diseases, maternal and child health, trauma and health care emergencies and access to care [ 40 ]. The UNICEF/UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases (TDR) currently has a large grant from the UK National Institute for Health Research (NIHR) to undertake and build capacity in operational research around the growing threat of antimicrobial resistance (AMR).…”
Section: Making Real-time Operational Research Happen and Ensuring It Is Effectivementioning
confidence: 99%
“…Mevcut gözlemsel çalışmalar incelendiğinde, sıklıkla bu çalışmaların raporlanmasında önemli bilgilerin mevcut olmadığı ya da açıkça belirtilmediği görülmektedir. Raporlama kılavuzlarının kullanımı, araştırmanın kalitesi ve güvenilir-liğinin artırılmasında önemli katkısı olduğu bildirilmektedir (5)(6)(7)(8). Raporlama kılavuzları, sağlık alanındaki araştırmacıların makalelerini yazarken belli bir akışı sağlayabilmeleri için kullanılan araçlardır.…”
Section: Introductionunclassified